2016
DOI: 10.3389/fphar.2016.00028
|View full text |Cite
|
Sign up to set email alerts
|

Plant Alkaloids as an Emerging Therapeutic Alternative for the Treatment of Depression

Abstract: Depression is a heterogeneous mood disorder that has been classified and treated in a variety of ways. Although, a number of synthetic drugs are being used as standard treatment for clinically depressed patients, but they have adverse effects that can compromise the therapeutic treatments and patient's compliance. Unlike, synthetic medications, herbal medicines are widely used across the globe due to their wide applicability and therapeutic efficacy associated with least side effects, which in turn has initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 26 publications
0
51
0
1
Order By: Relevance
“…In 2014, Dhingra and Valecha reported that punaravine ( 247 ) (Figure ), a quinolin‐4‐one alkaloid isolated from Boerhaavia diffusa , showed significant antidepressant activity in unstressed and stressed mice in different models . When compound 247 was administered orally for 14 successive days, immobility periods and sucrose preference were significantly decreased in both stressed and unstressed mice.…”
Section: Biological Activities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
“…In 2014, Dhingra and Valecha reported that punaravine ( 247 ) (Figure ), a quinolin‐4‐one alkaloid isolated from Boerhaavia diffusa , showed significant antidepressant activity in unstressed and stressed mice in different models . When compound 247 was administered orally for 14 successive days, immobility periods and sucrose preference were significantly decreased in both stressed and unstressed mice.…”
Section: Biological Activities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
“…They claimed that the anti-depressant and anxiolytic activity of Rasayana Ghana Tablet in ayurved is due to presence of β carboline alkaloid of TT which is the main contributor among 3 medicinal plants of Rasayana Tablet. It is observed that steroid phytochemical is responsible for hypoglycaemic activity in diabetic rats in C. papaya leaves 52 .…”
Section: Resultsmentioning
confidence: 99%
“…The isolated alkaloids showed antidiabetic and antioxidant potential in-vitro study 49 . Sadia Perviz et al, 2016 50 reviewed the antidepressant activity of β carboline alkaloid, a monoamine oxidase inhibitor in plants.…”
Section: Resultsmentioning
confidence: 99%
“…It is increasingly imperative to use the plant flavonoid glycosides as antimicrobial agents including antibiotic‐resistant gram‐positive and gram‐negative bacteria . Several studies have shown the antiviral activity of polyphenolic compounds; however, the mechanism underlying how flavonoids inhibit viral replication is not completely understood . Two flavonoids, 5,7,3′,4′‐tetra‐O‐methylquercetin and 3,4,5‐trihydroxyphenyl that are derived from elderberry fruit, showed a competitive inhibition of IAV virion entry to the host .…”
Section: Introductionmentioning
confidence: 99%
“…12,14,15 Several studies have shown the antiviral activity of polyphenolic compounds; however, the mechanism underlying how flavonoids inhibit viral replication is not completely understood. [16][17][18] Two flavonoids, 5,7,3′,4′-tetra-O-methylquercetin and 3,4,5-trihydroxyphenyl that are derived from elderberry fruit, showed a competitive inhibition of IAV virion entry to the host. 19 In the current work, we are interested to investigate and identify anti-influenza inhibitors via screening of naturally occurring products from plants, such as guava and lemon extracts.…”
mentioning
confidence: 99%